2015
DOI: 10.1039/c5ra16346c
|View full text |Cite
|
Sign up to set email alerts
|

Cycling of waste fusel alcohols from sugar cane industries using supercritical carbon dioxide

Abstract: The present study describes the clean synthesis of non-phosgene organic carbonates (NPOCs) from a selective multicomponent reaction with two important by-products from sugar and alcohol industries, namely, fusel alcohols and carbon dioxide, in the presence of 1,8-diazabicycloundecene (DBU), 1,5-diazabicyclo[4.3.0]-non-5-ene (DBN) or 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]-pyrimidine (TBD) and an alkylating agent. The bases were used for the nucleophilic activation of the alcohols. The synthesis of carbonates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Plausible reaction mechanism . According to the previous reports, [35–38] as well as the experimental results obtained in this study, a plausible reaction mechanism has been proposed (Scheme 4). DBU can produce an unstable amidinium alkyl carbonate intermediate I [DBUH] + [R 1 OCOO] − by reacting with CO 2 and alcohol [29,41–43] .…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Plausible reaction mechanism . According to the previous reports, [35–38] as well as the experimental results obtained in this study, a plausible reaction mechanism has been proposed (Scheme 4). DBU can produce an unstable amidinium alkyl carbonate intermediate I [DBUH] + [R 1 OCOO] − by reacting with CO 2 and alcohol [29,41–43] .…”
Section: Resultssupporting
confidence: 71%
“…In the 1990s, McGhee et al [35,36] developed organic superbases-promoted synthesis of organic carbamate or carbonate from CO 2 and amine or alcohol. Pereira et al [37] reported the synthesis of organic carbonates from fusel alcohols and CO 2 in the presence of DBU and an alkylating agent. Shang et al [38] reported the guanidine-promoted direct synthesis of open-chained carbonates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37] Carbonate esters of isoamyl alcohol have been previously prepared such as its reaction in supercritical carbon dioxide with n-butyl bromide and 1,8-diazabicycloundecene as base to form isoamyl n-butyl carbonate. 38 However, dimethyl carbonate (DMC) has become a widely available solvent/reagent that can serve as a synthetic equivalent of carbon dioxide. 39,40 The mixed isoamyl methyl carbonate, for nail polish removal, 41 was made by potassium carbonate catalyzed reaction of isoamyl alcohol with excess DMC.…”
Section: Hydrocarbon Base Oil Solubility In Alcoholmentioning
confidence: 99%
“…Particularly appealing is the use of carbon dioxide and its sequestering into the chemical structure of recirculated products. 183 The use of wastes and recycled materials might be an uncomfortable concept for research chemists who deal with pure, refined chemical intermediates, but this position is being eroded away with time as innovative examples begin to appear in the literature, 184 especially in materials science. 185 The opinion of industry is quite different, with companies increasingly looking to supplement the revenue from their traditional (and sometimes declining) business by valorising their waste stream.…”
Section: Outlook For a Sustainable Chemical Industrymentioning
confidence: 99%